A Eclesiologia do Código de Direito Canônico - Hackmann, Geraldo Luiz Borges (Revista Eclesiástica Brasileira, 2007)
O artigo reflete sobre a relação entre o Código de Direito Canônico e a Eclesiologia, mostrando que o ordenamento jurídico da Igreja é uma dimensão necessária da natureza e da missão da Igreja. Dois aspectos mostram essa relação: o mistério da Igreja e a imagem bíblica de Povo de Deus. Mas é preciso, ainda, aludir às categorias de sacramentalidade e de comunhão, além da dimensão institucional, para estabelecer mais profundamente a natureza e a missão específicas do Direito na Igreja. Abstract: This paper deals with the relation between the Code of Canonical Right and the Ecclesiology, showing that the Church’s juridical order is a necessary dimension belonging to the Church’s nature and dimension. By two aspects is shown this relation, namely the mystery and the biblical image of God’s people. But is also necessary, on the one hand, to allude to the categories of sacramentality and communion, and on the other hand to the institutional aspect, in order to establish more profundly the specific nature and mission of the Right of the Church.